Rancang Bangun Sistem Pengadukan Dan Pemantauan Suhu Kelembaban Pada Pupuk Kompos Berbasis Esp32 - Rafael, Rafael Dwi Prasetiyo; Rini Puji Astutik (Elkom: Jurnal Elektronika dan Komputer, 2024)
This research aims to design and build a system for stirring and monitoring temperature and humidity for ESP32-based compost fertilizer. This system uses an ESP32 microcontroller to control compost mixing and monitor temperature and humidity conditions in real- time. Data obtained from sensors will be sent to the server for monitoring via Blynk. The implementation of this system is expected to increase the efficiency of the composting process and produce high quality compost through optimal monitoring and mixing.